Impacts of climate change on Swiss alluvial aquifers – A quantitative forecast focused on natural and artificial groundwater recharge by surface water infiltration - Jannis Epting; Love Råman Vinnå; Sebastiano Piccolroaz; Annette Affolter; Stefan Scheidler (Journal of Hydrology X, 2022)
The sensitivity of future groundwater recharge and temperature development was investigated for three alluvial aquifers in the urban agglomeration of the city of Basel, Switzerland. For selected climate projections groundwater recharge and the associated temperature imprinting of aquifers, which are mainly determined by artificial groundwater recharge and infiltrating surface water, were investigated.3D numerical groundwater flow and heat-transport modeling, allowed quantifying and differentiating between natural and artificial groundwater recharge and thermal impacts. For aquifers where the infiltration of river water is an important component in the groundwater balance, the effects of climate change will be influenced by changes in river flow and thermal regimes and also by artificial groundwater recharge of surface water. Considering all climate scenarios investigated, the net heat input from river water infiltration for the Lange Erlen case study area increases by an average of 42 % by 2055 and 62 % by 2085 compared to the reference year 2000. Together with further heat inputs, particularly by artificial groundwater recharge, the temperatures of the extracted drinking water would increase by 0.4 to 1.3 K by 2055 and 0.7 to 3.1 K by 2085. In the Hardwald case study area, the most significant heat exchange occurs by artificial groundwater recharge. As a result, and considering all climate scenarios investigated, heat loss by groundwater extraction increases by an average of 38 % during the winter months from the year 2000 to the year 2085. The increased heat input, especially in the summer months, results in a temperature increase of the extracted drinking water of 0.2 to 1.0 K by 2055 and 0.6 to 4.0 K by 2085. In the Lower Birs Valley case study area, net heat input from river water infiltration increases by an average of 42 % by 2055 and 62 % by 2085. Correspondingly, the temperatures of the extracted drinking water increase by 0.9 to 3.2 K by 2055 and by 0.3 to 5.4 K by 2085.The quantitative assessment of climate change impacts on the groundwater resources presented allows to differentiate between hydraulic and thermal impacts of natural and artificial groundwater recharge processes. Accordingly, individual drinking water wells are exposed differently to the various components of groundwater recharge. Seasonal shifts in natural groundwater recharge processes and adaptation strategies related to artificial groundwater recharge could therefore be an important factor affecting groundwater resources in future. Moreover, increased groundwater recharge from artificial groundwater recharge systems in summer months and the interaction with surface waters during high runoff periods, which will occur more often in winter months, are likely to strongly influence groundwater recharge and temperatures.